Various Methods of Reducing Calcium Oxalate Levels in Tubers: a Review - Ati Atul Quddus; Erliza Hambali; Mulyorini Rahayuningsih; Ika Amalia Kartika; Slamet Budijanto (Biota, 2024)
Tubers, as a highly promising agricultural commodity with distinctive flavors and nutritional content, pose health challenges due to the presence of calcium oxalate. Excessive consumption can lead to mechanical disturbances in the digestive and renal tubule systems. This complicates processing techniques to ensure that tubers, before being used as raw materials in the food and other industries, do not contain calcium oxalate. The research method involves a literature review, in-depth exploration of theories and concepts, and identification of variables related to the research method and context. From the literature study, it is evident that focusing on understanding fermentation parameters, such as time, temperature, pH, and the type and concentration of microorganisms, is crucial. This information is expected to provide insights into potentially effective methods for reducing calcium oxalate content in tubers, supporting the development of safer and healthier agricultural and food processing practices.